Costs of criminal proceedings in the light of some empirical data (Discourse of Law and Administration, 2021)
The publication is devoted to the problem of criminal proceedings costs. It presents the results of research showing how much the average criminal trial costs, what factors have a major impact on its cost, how this issue is arranged depending on the level of the court or its location, what impact on the costs of criminal proceedings is played by consensual methods of termination an trial. The presented in this publication research were financed entirely thanks to the funds allocated for this purpose by the National Science Center, under the contract for the implementation of the project entitled „The costs of criminal proceedings in the light of the economic analysis of law” (contract no. UMO-2015/19/B/HS5/01217).
Keywords: criminal trial; costs of proceedings; economic analysis of law; legal assistance; effectiveness of proceedings